2020
DOI: 10.1016/j.ijpddr.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of a new chloroquine analog in an animal model of Leishmania panamensis infection

Abstract: Leishmania panamensis is a relevant causative agent of tegumentary leishmaniasis in several Latin American countries. Available antileishmanial drugs have several limitations including relatively high toxicity, difficult administration, high production costs and the emergence of resistance in circulating strains. Therefore, the identification of new molecules as potential therapeutics for leishmaniasis is of great relevance. Here, we developed a murine model of L. panamensis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This similarity further supports the use of BALB/c mice as the preferred model for studying L . panamensis immunopathogenesis and evaluating potential drug candidates [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This similarity further supports the use of BALB/c mice as the preferred model for studying L . panamensis immunopathogenesis and evaluating potential drug candidates [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania panamensis PSC-1 strain (MHOM/PA/1994/PSC-1) promastigotes were axenically maintained in Schneider’s insect medium (Sigma-Aldrich, St. Louis, MO, USA) at pH 7.2 supplemented with 20% (v/v) heat-inactivated fetal bovine serum (Gibco, Gaithersburg, MD, USA), 50 μg/mL gentamicin (Sigma-Aldrich, St. Louis, MO, USA), and incubated at 25 °C. Parasites were previously adapted to mice by serial passages in the hind footpad of BALB/c mice for a period of 24 months [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further studies showed that these derivatives inhibit the production of IL-10 by macrophages infected with Leishmania , suggesting that the compound-induced parasite-killing mechanism may be associated with the regulation of macrophage activation. Four years later, in 2020, the same research group evaluated derivative 37 in an animal model of L. panamensis infection, which corroborated this compound’s potential against Leishmania and the compound-induced inhibition of IL-10 production by macrophages [ 37 ].…”
Section: Quinolines As Antileishmanial Agentsmentioning
confidence: 93%
“…In this respect, chloroquine combined with diminazene merited further development [ 17 ]; however, the combination with paromomycin did not yield encouraging results [ 18 ]. Several chloroquine derivatives have been evaluated on Leishmania models in vitro and in vivo [ 19 ]. However, the major source of drug candidates was the 8-aminoquinoline series.…”
Section: The Place Of Quinolines As Drug Candidates In the Treatment ...mentioning
confidence: 99%